Using co-design to create user-friendly material promoting cardiac rehabilitation. (2nd July 2022) - Caughers, G; Wilson, A; Donnelly, P; Bradley, J; Fitzsimons, D
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Public Health Agency Northern Ireland, Research and Development PhD Fellowship Background: Cardiac Rehabilitation (CR) participation rates remain stagnant across Europe at around 40%(1), with similar low uptake in Northern Ireland. Patients in our Steering Group confirmed that misconceptions about CR and lack of clear explanations negatively influence their decision to attend. Patients can feel overwhelmed by the experience of a cardiac event and the importance of CR is easily overlooked. Co-production of a short information film could better inform patients, family and the public. Methods: Focus groups and interviews with N=58. Patients and carers informed 2 co-design workshops identifying the need for an information film to be available to cardiac patients and their families. Between July and November 2021, virtual multidisciplinary staff and patient groups developed the film with all members contributing to the script, voice content and film footage. A professional film company produced the 90 second infomercial with direction from patients and CR professionals. Results: The information film portrays the experiences of a male and female patient. Elements of CR that were perceived as attractive components by patients in the codesign workshops are portrayed including; one to one interactions between staff and patients, the diversity of CR teams, and comradery between patients. The film is designed to be viewed on multiple devices, in hospital and at home following discharge. Conclusion: Providing information about CR through the media of film may help to dispel misconceptions of CR and promote its attractiveness to patients. The effectiveness of this film awaits evaluation following dissemination to staff and patients this year.